Comparison of EOG and VOG obtained eye movements during horizontal head impulse testing - Pleshkov, Maksim; Zaitsev, Vasilii; Starkov, Dmitrii; Demkin, Vladimir; Kingma, Herman; van de Berg, Raymond (Frontiers in Neurology, 2022)
Introduction. Video Head Impulse Testing is frequently used to evaluate the vestibular function. During this test, eye movement responses are recorded with video-oculography (VOG). However, the use of VOG can sometimes be challenging, especially due to pupil detection problems (e.g. blinking, droopy eyelids, etc.). Therefore, this study investigated whether electro-oculography (EOG), a technique which does not depend on pupil tracking but on the orientation of the corneo-retinal potential, might be an alternative to VOG for quantifying eye movement responses during head impulse testing. Subjects and Methods. Head impulse testing was performed in 19 healthy subjects without a prior history of vestibular symptoms. Horizontal eye movements were recorded simultaneously with EOG (using an EOG system) and VOG (using a VHIT system: ICS Impulse). The eye movement responses to each side of both techniques were compared using a concordance correlation coefficient (r_c), t-testing and Bayes Factor (BF) paired t-testing. Results. EOG and VOG obtained eye movement traces correlated well with each other during head impulse testing (average r_c=0.89). Average VOR gains obtained with EOG and VOG were not significantly different from each other for all subjects during left head impulses. However, VOG gains differed between both techniques regarding right head impulses. VOG showed significant VOR gain asymmetry (5% to the right), whereas EOG indicated 1% not significant asymmetry to the right. Conclusion. This study demonstrated for the first time the use of EOG to record eye movements during head impulse testing. EOG and VOG obtained eye movement traces correlated well with each other during horizontal head impulse testing. In addition, EOG showed smaller VOR gain asymmetry in healthy individuals, in contrast to VOG. These findings indicate that EOG might potentially be applicable as an alternative to VOG for collecting eye movement responses during head impulse testing.